Analisis Pelayanan Publik pada Kepolisian Daerah Bengkulu (Studi pada Sentra Pelayanan Kepolisian Terpadu) - Aprianty, Henny; Ichwan, Muhammad; Dani, Rahiman; Purnawan, Heru; Triyanto, Deni (Jurnal Publisitas, 2025)
This study analyzed public services in the Bengkulu Regional Police environment with a survey at the Integrated Police Service Center. The type of research used in this study is qualitative research. This study presents a descriptive discussion of the research with a case study technique that is carried out intensively, in detail, and in-depth on the object of research, the data in this study were obtained from primary data and secondary data. The data collection techniques used were observation methods, interview methods, and documentation methods. The data analysis techniques used were Data Reduction, Data Display, and Conclusion Drawing/Verification. The results of the study showed that in general the service at the Bengkulu Regional Police SPKT was good and met public service standards. Simple administrative requirements, easy-to-access service systems, efficient service times, and public complaints were handled quickly and transparently. The public was also satisfied with the professional and friendly attitude of the officers. However, there are still several aspects that need to be improved, such as the use of information technology, further training for officers, increasing the number of personnel during peak hours, and strengthening supporting facilities such as special rooms for vulnerable groups. With improvements in these aspects, the quality of Bengkulu Police SPKT services is expected to be more optimal, responsive, and oriented towards public satisfaction..